UMP, POLISAS forge strategic partnerships in T&L, research, publications and services - Safriza, Baharuddin (2021)
KUANTAN, 24 August 2021 - Universiti Malaysia Pahang (UMP) and Politeknik Sultan Haji Ahmad Shah (POLISAS), Kuantan recently entered into a strategic partnership in sharing expertise and knowledge services to students and lecturers for teaching and learning activities (T&L) and research.